‘AND EARTH, SEA, MAN, ARE ALL IN EACH’: AN ECOCRITICAL STUDY OF DANTE GABRIEL ROSSETTI’S SELECTED POEMS - Islam, Md. Zohorul (Universitas Pendidikan Ganesha, 2021)
Ecocriticism or Green Study emerged in the field of literature in the late 20th century where the relationship between literary text and physical environment is explored. The recent human actions and environmental degradation have encouraged human beings to explore the ecological visions of the authors from different genres. The industrial revolution in the Victorian era brought enormous changes in society, and literary texts were produced concerning ecological degradation or celebrating the relationship between human beings and nature. Dante Gabriel Rossetti's vision toward establishing the connection between humans and the physical environment is an important aspect of the ecocritical study. Ecocriticism has been widely viewed as a field of study where environmental awareness can be raised through the theoretical study of literary texts. Therefore, this paper aims at exploring Dante Gabriel Rossetti’s selected poems from an ecocritical point of view. Rossetti's poems represent a significant amount of human-nature interaction and nature’s enormous healing power to the eco-system. This study also aims at growing the ecological consciousness of the readers in a world where it is going through a phase of life-threatening climate change.